2010
DOI: 10.1097/eja.0b013e32833cad40
|View full text |Cite
|
Sign up to set email alerts
|

Does isolation technique have any impact on inhalational exposure of neuroanaesthetists to sevoflurane during craniotomies?

Abstract: IntroductionThere are multiple reports of the use of vasopressin with phaeochromocytoma resections in adults. Support for vasopressin in the paediatric patient, however, is not quite as substantiated. We report such a case to add to the limited evidence for its use in a young child. Case reportA 6-year-old boy, weighing 21 kg, was admitted to a local District General Hospital with severe headaches not responding to simple analgesics. His initial blood pressure was recorded as 166/91 mmHg. This was persistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…1, when a laminar system is used, the gas flow is driven toward the anesthetist located at the side of the patient. As we proved previously during our measurements, the main source of sevoflurane evaporation is the patient’s mouth [7] and the proximity of the anesthetist located at the side contributes to higher exposure due to the open isolation drape driving the evaporated gas toward the anesthetist [8]. Therefore, the open isolation along with the air flow due to the laminar system may result in higher anesthetic exposure for the sitting anesthetist (See Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…1, when a laminar system is used, the gas flow is driven toward the anesthetist located at the side of the patient. As we proved previously during our measurements, the main source of sevoflurane evaporation is the patient’s mouth [7] and the proximity of the anesthetist located at the side contributes to higher exposure due to the open isolation drape driving the evaporated gas toward the anesthetist [8]. Therefore, the open isolation along with the air flow due to the laminar system may result in higher anesthetic exposure for the sitting anesthetist (See Fig.…”
Section: Discussionsupporting
confidence: 51%
“…In a previous study it was also proven that positioning of anesthesia at the feet of the patient (rather than at the side) may decrease anesthetic exposure [8]. However, in some institutions anesthetists insist on positioning anesthesia team at the side because, in their judgment, the patient is better accessible this way.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Tankó et al revealed that during intracerebral surgeries, the evaporated amount of sevoflurane is the highest at the anesthetist's breathing zone, the most important source of this leakage is the patients' mouth [4] and the amount of evaporated gas is independent of the endotracheal tube cuff pressure [5]. It has been also demonstrated that exposure of the anesthesia staff can be decreased by proper positioning of the anesthesia personnel during intracranial surgery [6].…”
Section: How Can Anesthetic Gases Get Into the Air Of Operating Rooms?mentioning
confidence: 99%